AKINETIC MUTISM AS A NEUROPSYCHIATRIC SYMPTOM OF PROGRESSIVE MULTIFOCAL LEUKOENCEPHALOPATHY : A COMPLICATIONS OF HUMAN IMMUNODEFICIENCY VIRUS (HIV) INFECTION - Kartikasari, Desy; Tamasse, Jumraini; Joewana, Patricia GT; Putri, Maria PD (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
Progressive Multifocal Leukoencephalopathy (PML) is a rare complication of Human Immunodeficiency Virus (HIV) infection. The disease carries a poor prognosis, with rapid progression and death usually occurring within 6 months. Mental disorders are a fairly common symptom in patients with PML (1/3 of cases). A 39-year-old male came with akinetic mutism. He has difficulty communicating, is unwilling to speak, has lost voluntary movements, and lacks motivation and initiative to perform daily activities. Managing this case is quite challenging, requiring careful history taking, physical examination, and selecting appropriate supporting tests. The management of this case involves a neurologist, internist, psychiatrist, and nutritionist. Correct diagnosis and treatment lead to clinical improvement. On the 15th day of treatment, the patient began to speak briefly with his family. Furthermore, his sleep has improved. Recognising this rare case earlier can be a clinical experience if at some point a similar case is found.